2017
DOI: 10.1037/bne0000199
|View full text |Cite
|
Sign up to set email alerts
|

Child gender influences paternal behavior, language, and brain function.

Abstract: Multiple lines of research indicate that fathers often treat boys and girls differently in ways that impact child outcomes. The complex picture that has emerged, however, is obscured by methodological challenges inherent to the study of parental caregiving, and no studies to date have examined the possibility that gender differences in observed real-world paternal behavior are related to differential paternal brain responses to male and female children. Here we compare fathers of daughters and fathers of sons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 73 publications
1
61
0
5
Order By: Relevance
“…We have also designed new, project-specific modules to capture, for example, breast cancer survivors' interactions with their support networks (e.g., positive and negative received support; Robbins et al, 2014), and pro-social behaviors in the context of meditation training (gratitude, affection; Kaplan et al, 2018). In recent projects, we have further expanded the SECSI system to assess family-level environments and interactions (e.g., Alisic et al, 2015;Mascaro, Rentscher, A PRACTICAL GUIDE TO CODING AND PROCESSING EAR DATA 8 Hackett, Mehl, Rilling, 2017), which required significant modifications to the basic coding system in order to capture the complexities of daily family life. Examples of these and other coding systems are available by request and as part of the OSF EAR Repository.…”
Section: Figure 1 Steps To Coding and Processing Ear Data Ear Codingmentioning
confidence: 99%
“…We have also designed new, project-specific modules to capture, for example, breast cancer survivors' interactions with their support networks (e.g., positive and negative received support; Robbins et al, 2014), and pro-social behaviors in the context of meditation training (gratitude, affection; Kaplan et al, 2018). In recent projects, we have further expanded the SECSI system to assess family-level environments and interactions (e.g., Alisic et al, 2015;Mascaro, Rentscher, A PRACTICAL GUIDE TO CODING AND PROCESSING EAR DATA 8 Hackett, Mehl, Rilling, 2017), which required significant modifications to the basic coding system in order to capture the complexities of daily family life. Examples of these and other coding systems are available by request and as part of the OSF EAR Repository.…”
Section: Figure 1 Steps To Coding and Processing Ear Data Ear Codingmentioning
confidence: 99%
“…Boys, as compared to girls, are more likely to be the target of aggression by abusive fathers (Jouriles & Norwood, ). A recent study found that fathers interacted differently with their sons and daughters, engaging in more rough and tumble play with their sons while singing more to their daughters (Mascaro, Rentscher, Hackett, Mehl, & Rilling, ). These behavioral differences corresponded with different patterns of brain activation in response to their child's facial expressions (Mascaro et al, ), suggesting a biological underpinning of these gender differences in caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that fathers interacted differently with their sons and daughters, engaging in more rough and tumble play with their sons while singing more to their daughters (Mascaro, Rentscher, Hackett, Mehl, & Rilling, ). These behavioral differences corresponded with different patterns of brain activation in response to their child's facial expressions (Mascaro et al, ), suggesting a biological underpinning of these gender differences in caregiving. It is unclear how a two‐parent dynamic could contribute to outcomes of caregiver experience in human populations.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de ello, el estudio brinda información de dos de las áreas temáticas más relevantes del desarrollo socioemocional de niños y niñas en edad preescolar y reporta resultados coherentes con las evidencias teóricas y empíricas actuales (Rothbart & Bates, 2006). Para futuras investigaciones, se recomienda incorporar variables del entorno como las prácticas de crianza familiar (Mascaro, Rentscher, Hackett, Mehl, & Rilling, 2017;Olson, Lopez-Duran, Lunkenheimer, Chang, & Sameroff, 2011;Raya, Pino, & Herruzo, 2009), el vínculo con las figuras de apego (Hong & Park, 2012) o la socialización de los roles de género (Olino et al, 2013).…”
Section: Discussionunclassified